U.S. counterterrorism: from Nixon to Trump : key challenges, issues, and responses - Kraft, Michael B. (CRC Press, 2018)
Overview of the terrorism threat from Nixon to Trump -- Terrorism definitions, sanctions and legislations -- Background: Nixon to Clinton -- Changes in CT policy in Bush administration following 9/11 -- Obama administration: policy and program responses -- The policy challenges for the Trump administration